2004
DOI: 10.1161/01.str.0000147716.45571.45
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Neuroendocrine Dysfunction in Long-Term Survivors of Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-To investigate the incidence, pattern, and magnitude of neuroendocrine changes in long-term survivors of aneurysmal subarachnoid hemorrhage (SAH). Methods-Thirty patients (16 women) with a mean age of 50Ϯ13 years underwent endocrine assessment between 12 and 24 months after aneurysmal SAH. SAH severity was graded clinically by the Hunt & Hess scale (median, II) and radiologically by the Fisher classification (median, II). Patients underwent measurement of basal hormone levels and dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
118
7
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(140 citation statements)
references
References 23 publications
13
118
7
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8]12 The first large multicenter study on SAH patients was carried out by Aimaretti and colleagues who investigated 40 patients three months after SAH and diagnosed a variable degree of hypopituitarism in 37.5% of the patients. 5 In contrast to TBI, pituitary deficits after SAH are more often isolated than multiple and panhypopituitarism has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8]12 The first large multicenter study on SAH patients was carried out by Aimaretti and colleagues who investigated 40 patients three months after SAH and diagnosed a variable degree of hypopituitarism in 37.5% of the patients. 5 In contrast to TBI, pituitary deficits after SAH are more often isolated than multiple and panhypopituitarism has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Pituitary insufficiency in a patient after SAH caused by the rupture of an aneurysm of the anterior communicating artery was published in 1961 by Hoff et al 7 Kelly and colleagues reported pituitary insufficiency after SAH in two patients 3.5 and 13 months, respectively, after aneurysmal SAH. 1 These patients presented with Growth Hormone Deficiency (GHD) diagnosed by Insulin Tolerance Test (ITT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both treatment groups exhibited cognitive impairments in memory, attention and speed of information processing (4). Previous clinical studies have indicated that long-term survivors of aSAH frequently exhibit hypothyroidism (5,6). Furthermore, cognitive dysfunctions in these patients resemble the disruptions observed in patients with hypothyroidism.…”
Section: Introductionmentioning
confidence: 85%
“…A number of studies, often incorporating patients with both SAH and traumatic brain injury (TBI), have concluded that hypopituitarism is common in this patient group (1,2,3,4,5), with a systematic review by Schneider et al in 2007 (6) concluding that hypopituitarism is present in 47% of patients in the chronic phase after SAH. In contrast, Klose et al (7), evaluating 61 patients prospectively, concluded that SAH was uncommon having failed to identify a single case.…”
Section: Introductionmentioning
confidence: 99%